Conservation agriculture revisited: mapping its carbon sequestration potential in African soils - Biratu, Gizachew Kebede; Getaneh, Fite; Moges Kidane Biru; Niguse Bekele Dirbaba; Gameda, Samuel; Thierfelder, Christian; Sida, Tesfaye Shiferaw (2025)
Soil is considered both the source and sink of carbon, depending on management. Conservation agriculture (CA) has been largely implemented to stabilize crop yield but provides the co-benefit of soil organic carbon (SOC) sequestration. Nevertheless, there are controversies surrounding its potential in sub-Saharan Africa (SSA). Using spatially disaggregated approach, we showed that CA can offer a SOC sequestration potential of 26.7 Tg SOC yr⁻¹ across maize and wheat-based systems, with estimated rates ranging from –1.37 to 3.98 Mg ha⁻¹ yr⁻¹ across SSA. This potential is highly variable depending on the intensity of CA practices, soil texture, and climatic zones. For instance, no-till for maize system alone may sequester about 30.5 Tg yr⁻¹ on medium-textured soils in humid environments, while CA- diversification can lead to negative SOC balances depending on the context. These findings highlight the spatially heterogeneous nature of CA outcomes, underscoring the need for targeted, context-specific strategies to maximize climate mitigation benefits.